Science, Art and Inner Culture - Gaidamavičienė, Irena (Problemos, 1984)
The concept “spiritual culture” is not adequate to the term “inner culture”. The former includes scientific character and science itself, art and axiological-aesthetical sense of beauty, the latter is more related to spiritual potency which is not acquired but inherited (P. K. Anokhin shares this view). Art, contrary to science does not simulate objective reality but discloses subjective experience and subjective sense in relation to objective reality. It is more related to inner culture. In socialist society there exist more possibilities for the development of aesthetical and scientific level of life and therefore for the formation of inner culture of the masses.